Ultrafine MoS2 Nanosheets Vertically Patterned on Graphene for High-Efficient Li-Ion and Na-Ion Storage - Wei, Chunguang; Hou, Zhidong; Sun, Huanhuan; Wang, Jian-Gan (Frontiers in Chemistry, 2021)
Hierarchically two-dimensional (2D) heteroarchitecture with ultrafine MoS2 nanosheets vertically patterned on graphene is developed by a facile solvothermal method. It is revealed that the strong interfacial interaction between acidic Mo-precursors and graphene oxides allows for uniform and tight alignment of edge-oriented MoS2 nanosheets on planar graphene. The unique sheet-on-sheet architecture is of grand advantage in synergistically utilizing the highly conductive graphene and the electro-active MoS2, thus rendering boosted reaction kinetics and robust structural integrity for energy storage. Consequently, the heterostructured MoS2@graphene exhibit impressive Li/Na-ion storage properties, including high capacity delivery and superior rate/cycling capability. The present study will provide a positive impetus on rational design of 2D metal sulfide/graphene composites as advanced electrode materials for high efficient alkali-metal ion storage.